Career Development of Islamic Religious Education Lecturers at State Universities - Hidayatulloh, Furqon Syarief (Atthulab: Islamic Religion Teaching and Learning Journal, 2022)
The development of Islamic Religious Education/ PAI lecturers at state universities (non-religious public institutions of higher education). Depends on how the university locates the PAI institution. The purpose of this study is to find out the model for developing Islamic Religious Education lecturers at state universities. This research was conducted using a case study approach at the Bogor Agricultural Institute, which turned out to be the only university that implemented the homebase departmental model. The data collection process was carried out through in-depth interviews, document analysis, and participatory observation. From the results of the research, it is known that with this model PAI lecturers are involved in the Tri Dharma College educational activities in a planned and consistent manner like other general lecturers. In addition, in the field of education and teaching, PAI lecturers in teaching PAI courses are also involved in teaching majors-based science courses. PAI courses are also involved in student academic guidance, academic assistance and scientific writing, and examinations on various student examinations in majors. In the field of research and community service, PAI lecturers are involved in departmental-based research and are involved in the religious development of the academic community and the general public through the application of department-based science and technology. Â Pengembangan pendidikan agama Islam/dosen PAI di perguruan tinggi negeri (lembaga publik pendidikan tinggi non-agama). Tergantung pada bagaimana universitas menempatkan lembaga PAI. Tujuan dari penelitian ini adalah untuk mengetahui model pengembangan dosen Pendidikan Agama Islam di perguruan tinggi negeri. Penelitian ini dilakukan dengan menggunakan pendekatan studi kasus di Institut Pertanian Bogor, yang ternyata menjadi satu-satunya universitas yang menerapkan model departemen homebase. Proses pengumpulan data dilakukan melalui wawancara mendalam, analisis dokumen, dan pengamatan partisipatif. Dari hasil penelitian tersebut, diketahui bahwa dengan model ini dosen PAI terlibat dalam kegiatan pendidikan Tri Dharma Perguruan Tinggi secara terencana dan konsisten seperti dosen umum lainnya. Selain itu, di bidang pendidikan dan pengajaran, dosen PAI dalam mengajar mata kuliah PAI juga terlibat dalam pengajaran mata kuliah sains berbasis jurusan. Dosen PAI juga terlibat dalam bimbingan akademik mahasiswa, bantuan akademik dan penulisan ilmiah, dan ujian pada berbagai ujian mahasiswa di jurusan. Di bidang penelitian dan pengabdian kepada masyarakat, dosen PAI terlibat dalam penelitian berbasis departemen dan terlibat dalam pengembangan keagamaan civitas akademika dan masyarakat umum melalui penerapan ilmu pengetahuan dan teknologi berbasis departemen.